2001
DOI: 10.1021/jm001104n
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Benzothiazoles. 14. Synthesis and in Vitro Biological Properties of Fluorinated 2-(4-Aminophenyl)benzothiazoles

Abstract: Synthetic routes to a series of mono- and difluorinated 2-(4-amino-3-substituted-phenyl)benzothiazoles have been devised. Whereas mixtures of regioisomeric 5- and 7-fluoro-benzothiazoles were formed from the established Jacobsen cyclization of precursor 3-fluoro-thiobenzanilides, two modifications to this general process have allowed the synthesis of pure samples of these target compounds. Fluorinated 2-(4-aminophenyl)benzothiazoles were potently cytotoxic (GI(50) < 1 nM) in vitro in sensitive human breast MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(172 citation statements)
references
References 23 publications
4
167
1
Order By: Relevance
“…However, the potency of the compound was higher in HeLa cells than in MDA-MB-231 cells, because our assay lasted half the time that was reported for breast cancer cells. Likewise, our results are consistent with the antitumor effect for other benzothiazole-containing compounds such as fluorinated 2-phenylbenzothiazole derivatives with IC 50 values between 50 to 0.0001 µM [10], as well as 2-(4-Amino-3-methylphenyl) benzothiazole derivatives showed IC 50 values between 100 nM to 100 µM [13,14]. According to these data, the relative potency of this type of compound depends on the origin of the cancer cell line.…”
Section: In Vitro Citotoxicity Assay On Hela Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the potency of the compound was higher in HeLa cells than in MDA-MB-231 cells, because our assay lasted half the time that was reported for breast cancer cells. Likewise, our results are consistent with the antitumor effect for other benzothiazole-containing compounds such as fluorinated 2-phenylbenzothiazole derivatives with IC 50 values between 50 to 0.0001 µM [10], as well as 2-(4-Amino-3-methylphenyl) benzothiazole derivatives showed IC 50 values between 100 nM to 100 µM [13,14]. According to these data, the relative potency of this type of compound depends on the origin of the cancer cell line.…”
Section: In Vitro Citotoxicity Assay On Hela Cellssupporting
confidence: 90%
“…Recent studies showed that this compound and its analogues promote signaling and nuclear translocation of Aryl hydrocarbon Receptor (AhR) and induce the carboxyl terminus of Hsp70-interacting protein (CHIP) expression through recruitment of AhR upstream of the CHIP gene. This mechanism has potential application in the suppression of tumor progression in breast cancer cells [13][14][15][16][17]. The synthesis of the title compound has been recently improved by using several catalysts such as LiBr [18], ZnO [19] and CdS [20], silica [21], nanoparticles, clays [22,23], and transition metals [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Benzothiazoles are well known to exhibit various biological properties including antimicrobial, anticancer, anti-amyloid, antirheumatic, and antiglutamate activities. [10][11][12][13] Various modified arylbenzothiazoles and substituted 2-aminobenzothiazoles are also known to possess significant anticancer activity both in vitro and in vivo. [14][15][16][17][18] Phenylcinnamide derivative 4 [19] induced G 2 /M-phase cell-cycle arrest and cell death in cancer cell lines at low micromolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compounds 9-15 vary from compounds 3-9 due to including chlorine atom on phenyl ring at second position of the benzothiazole structure. Imidazole including compounds namely N-[4-(benzothiazole-2-yl)phenyl]-2-[(1,5-diphenyl-1H-imidazole-2-yl)thio]acetamide derivatives (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) have methyl, methoxy and fluoro substituents on phenyl groups at the first and fifth positions of the imidazole ring. Among the nine tested compounds, imidazole and non-substituted benzimidazole including compounds (3, 10 and 16) possessed higher activity.…”
Section: Resultsmentioning
confidence: 99%
“…Phortress (NSC 710305, dihydrochloride salt of the lysylamide prodrug of 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (5F 203)), the fluorinated water-soluble pro-drug, which has been synthesized to address formulation and bioavailability issues related to the desired parenteral administration [15][16][17][18][19] , was then chosen for phase 1 The mechanism of action involves formation of reactive intermediates that can bind covalently to DNA and can be metabolized only by sensitive cancer cell lines 21 . Conversely, in insensitive cell lines, neither retaining nor metabolization occurs, thereby selective antitumor properties appear due through to metabolism [22][23][24][25][26] . Motivated by the above observations and extending our previous study 27 , we planned to synthesize new 2-(4-aminophenyl)benzothiazole derivatives including (benz)imidazole/benzoxazole/benzothiazole heterocyclic ring systems and to evaluate their antitumor activity against nine cancer types comprised of approximately 60 cell lines.…”
Section: Introductionmentioning
confidence: 99%